Posttreatment complications in the practice of Gynecological Radiotherapy Departament in Lodz. 2nd part - Sobotkowski, Janusz (Menopause Review/Przegląd Menopauzalny, 2003)
After general description of irradation sequelae in the first part of paper author analyses: what have been done and what is possible to do to avoid undesired effects of this kind of treatment. Optimisation of dose planning, accurate therapy procedures controling, choose of more precise treatment indications – these are some of important ways to decrease a complications occurence. The technical progress gives a valuable help in fight against cancer with relatively minor complications rate; for example using sources of very high acticity, what leads to shortening of treatment time, so some major effects as patient’s death don’t occur. Author described known, but not very widely used method of preoperative brachytherapy in cervical and endometrial cancer. It makes the teleradiotherapy not necesary in many patients and absence of related complications. Patient’s psychological well-being before treatment is of great importance. Constant care of hospital psychologist is a common practice in Gynecological Radiotherapy Dept. in Lodz.